ESTRATÉGIAS PARA AVALIAÇÃO DE UM PROGRAMA DE GINÁSTICA LABORAL: O CASO DE UMA PEQUENA INDÚSTRIA EM DUQUE DE CAXIAS -RJ - Mó, José Rogério Rodrigues (2009)
The study aimed at to identify as a program of Workforce Physical training, introduced in an industry, it can or not contribute for the reduction and / or elimination of the elements stimulators of the occupational diseases. This project is proposed to analyse the activities of the productive process using the methodology of the Ergonomic Analysing of the Work (EAW) and of the method Ovako Working Postures Analysing System (OWAS), aiming of identifying risks and disfuntions. For that, questionnaires carried out a study, which lifting data took place for observations registered in photos and spreadsheets of postures and, with the officials of the establishment, added of a selection of theoretical revision including the considered aspects. Through analyses of collected data, the inquiry shows with O case study shows that the adoption of the program of the above-mentioned gymnastics showed to be a positive way in the prevention of RSI/MSD, becoming, also, a way of developing the health and the quality of the workers' of the area of production of the organization life studied located in Duque de Caxias, state of Rio de Janeiro.The results of this study show, also that suggested simple measures, as: the) chairs with adaptation options and confortabilidade; b) alternation with the dressmakers; c) substitution of the large knife for a guillotine in the sense of reducing the effort and the force spent with the large knife; and, d) rest adoption for the feet, they would also produce the employees' larger well-being.